Humiliated silence: multiculturalism, blame and the trope of ‘moving on’ - Emma Waterton (Museum & Society, 2010)
The issue of slavery has received wide media attention in response to the bicentenary of the abolition of the slave trade. Simultaneously, issues of multiculturalism and social exclusion have also been subject to tense debate. This paper aims to examine the rhetorical resources drawn upon at the juncture of these two areas of debate, particularly in terms of how the ‘slave trade’ and its abolition is understood, constructed and remembered. In order to examine how these issues are manifest, the paper utilizes critical discursive methodologies, which are applied to institutional and ‘official’ responses to the bicentenary of 1807. This data will be examined in terms of the discursive strategies drawn upon to actively absolve current generations from challenging the latent issues of power operative within modern British society.